ANALISIS PRIORITAS PENANGANAN KREDIT BERMASALAH DALAM RANGKA MENYEHATKAN KUALITAS KREDIT PADA BANK PERKREDITAN RAKYAT - Wangsit Supeno (Universitas Bina Sarana Informatika, 2017)
Credit is the biggest earning assets and the main source of income BPR. Loans have the risk of causing damage if not properly managed. Performance of Rural Bank lending can be seen from the quality of the non-current loans which amount does not exceed 5% of the total loan portfolio overall. In granting loans, the Management of Rural Banks must apply the principle of sound lending, since the credit is processed until the loan has been granted. Management of Rural Banks provide credit should conduct risk identification selectively applying Accurate Credit Analysis 5C, so expect credit credit default resulting in a stalemate in the future can be suppressed. Nonperforming loans at Rural Bank can be sourced from External and Internal, also because of weak monitoring and credit monitoring. On the other hand, factors stiff competition led to the precautionary principle does not run well, in which they perform less selective Credit Analysis so that the risk of a credit crunch with a substandard quality are very prominent. These conditions would have to be a management concern Rural Bank. In efforts to address problem loans management have to prioritize the completion of systematic and sustainable way. Rural Bank should monitor actively as a preventive measure to prevent non-performing loans to a standstill. Management must take action when borrowers found the problem and find solutions before the completion of credit into the quality of the jam. Management should set priorities for handling problem loans by putting in a family approach in the appeal of taking legal action. Credit Banks rescue people can do credit to a debtor in value can still be saved by way Rescheduling, Reconditioning and Restructuring. Rural Bank management can take action to remove the book if credit has been stalled quality and have attempted to meneyelesaikan but have not been successful. Priority settlement of non-performing loans were made consistently and continuously expected to restore the credit performance of Rural Bank, where credit quality is healthy so the development of productive assets and income from year to year continues to increase. Keywords: Non Performing Loans, Credit Quality